Consumo de vegetales y factores relacionados en estudiantes universitarios de la ciudad de Medellín, Colombia (2013)
ABSTRACT: To know vegetable intake and its related factors is important, in order to design programs that promote these food intake. Objective: To describe vegetable intake and its related factors in undergraduates by gender, socioeconomic status, and type of university (public vs. private). Materials and methods: 420 undergraduates, male and women, participated in a descriptive, exploratory and multidimensional cross sectional study. A FFQ that included 52 vegetables and a questionary to explore preferred taste and recipes were apply to each participant. A multivariate analysis of variance (MANOVA) with type canonical orthogonal contrast was used to analysis data. Results: Women include a higher number of vegetables in their diets than men (P=0.0142), however the total amount of vegetables ingested was similar between genders P=0.8589). The lowest vegetable intake was found in the lowest socioeconomic stratum (p=0.0065), and in undergraduates from public universities (P=0.0354). Conclusions: vegetable intake in undergraduates from Medellin is low. It is especially low in undergraduates from public universities and from low socioeconomic strata; which reflects inequality in vegetables intake. Key words: food consumption, vegetables, health food, food preferences, student, Colombia.